Preparation of low-concentration H2 test gas mixtures in ambient air for calibration of H2 sensors - Karbach, Niklas; Höhler, Lisa; Hoor, Peter; Bozem, Heiko; Bobrowski, Nicole; Hoffmann, Thorsten (Atmospheric measurement techniques, 2024)
Using electrochemical gas sensors for quantitative measurements of trace gas components in ambient air introduces several challenges, of which interference, drift and aging of the sensor are the most significant. Frequent and precise calibration as well as thorough characterization of the sensor helps to achieve reliable and repeatable results. We therefore propose the use of a simple, lightweight and inexpensive setup to produce hydrogen calibration gases with precisely known concentrations in ambient air. The hydrogen is produced by electrolysis with electric current monitoring, and the output can be set to any value between ∼ 3 and ∼ 11 µgH2min-1. With a dilution flow of 500 mL min−1, for example, this results in a concentration range from ∼ 70 up to ∼ 240 ppm, but concentrations significantly below or above this range can also be covered with accordingly modified dilution flows. This setup can be used not only for calibration, but also for thorough and long-term characterization of electrochemical gas sensors to evaluate sensitivity, zero voltage and response time over extended periods of time.